2008
DOI: 10.1007/s12237-008-9071-6
|View full text |Cite
|
Sign up to set email alerts
|

Community Oxygen and Nutrient Fluxes in Seagrass Beds of Florida Bay, USA

Abstract: We used clear, acrylic chambers to measure in situ community oxygen and nutrient fluxes under day and night conditions in seagrass beds at five sites across Florida Bay five times between September 1997 and March 1999. Underlying sediments are biogenic carbonate with porosities of 0.7-0.9 and with low organic content (<1.6%). The seagrass communities always removed oxygen from the water column during the night and produced oxygen during daylight, and sampling date and site significantly affected both night and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 48 publications
3
24
0
Order By: Relevance
“…Rates in Big Lagoon were comparable to measurements from other beds of H. beaudettei (Cotner et al, 2004;Yarbro and …”
Section: -1419supporting
confidence: 76%
“…Rates in Big Lagoon were comparable to measurements from other beds of H. beaudettei (Cotner et al, 2004;Yarbro and …”
Section: -1419supporting
confidence: 76%
“…As seagrass biomass increases with colonization time, it is expected that respiration rates would also increase , in part because of the high rates of bacterial metabolism fueled by increased organic matter (detritus, phytoplankton) deposition and decreased particle resuspension (Koch 1999;Gacia and Duarte 2001;Gacia et al 2002). Some previous studies and literature reviews have suggested that seagrass meadows are generally net autotrophic (Gattuso et al 1998;Hemminga and Duarte 2000;Gazeau et al 2005); however, it is also common for seagrass meadows to be either in metabolic balance as we found or net heterotrophic (Hemminga and Duarte 2000;Barron et al 2004;Yarbro and Carlson 2008). This variation is likely related to differences in environmental factors (light, nutrients, hydrodynamics), organic matter inputs, and self-shading within the seagrass canopy, and it is clearly important to capture these natural variations in order to understand patterns in trophic status correctly.…”
Section: Resultssupporting
confidence: 52%
“…The excretion of dissolved organic carbon (DOC), for instance, has been found to be slightly higher from the complex Zostera marina leaves-epiphytes than from the clean Z. marina leaves (Penhale & Smith, 1977). The balance also varies depending on season (Ziegler et al, 2004;Yarbro & Carlson, 2008;Barron & Duarte, 2009;Apostolaki et al, 2010) and time of the day. In the light, oxygen production through photosynthesis of seagrass leaves, epiphytes and algae usually counterbalances oxygen consumption through respiration and mineralization, resulting in carbon dioxide and nutrient uptake during daytime (Yarbro & Carlson, 2008).…”
Section: Introductionmentioning
confidence: 99%